Recommendations for the processing and storage of water samples before polymerase chain reaction (PCR) analysis - BJ Gilpin; M Devane; F Nourozi; B Robson; P Scholes; S Lin (New Zealand Journal of Marine and Freshwater Research, 2013)
A range of options for the storage and partial processing of water samples before polymerase chain reaction (PCR) analysis were evaluated. In addition, temporal storage of extracted DNA at 4 °C was investigated. Filtering the water sample and then storing that filter at −20 °C for up to six months before DNA extraction was equivalent to extracting DNA immediately. Freezing a water sample resulted in an immediate 1 log loss of PCR signal, although thereafter the sample was stable for at least three months. A rapid loss of detectable PCR product was found when storing a water sample at 4 °C for longer than one week. Extracted DNA could be stored at 4 °C for at least six months without considerable loss of PCR signal.